Produksi Konsentrat Protein dari Ampas Kelapa (Cocos nucifera L.) Menggunakan NaOH dan (NH4)2SO4 : Production of Protein Concentrate from Coconut Pulp (Cocos nucifera L.) using NaOH and (NH4)2SO4 - Hasdinda Hasdinda; Pasjan Satrimafitrah; Syaiful Bahri; Abd. Rahman Razak; Dwi Juli Puspitasari; Indriani; Aini Auliana Amar (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2023)
Coconut pulp wasted from processed coconut oil has a protein content of up to 18.20%. The potential coconut pulp protein can be processed in protein concentrate which has many benefits. This research was conducted to determine the effect of NaOH and (NH4)2SO4 concentrations in isolating protein and producing protein concentrates that have the highest yield and protein content. Isolation of coconut pulp protein was carried out using NaOH at several concentrations, namely 0, 0.2, 0.4, 0.6, 0.8, and 1 M, while the protein concentrate was prepared using the salting out method with a saturation level of the ammonium sulfate salt of 55%, 60%, and 65%. Analysis of protein content was carried out using the Kjeldahl method. The use of NaOH 0.2 M and (NH4)2SO4 with a saturation level of 60% was the chosen treatment with crude protein content and yield of 75.63% and 33.83%, respectively.